2014
DOI: 10.1159/000368885
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Dose and Risk Factors for Death Among ESRD Patients Treated with Twice-Weekly Hemodialysis: A Prospective Cohort Study

Abstract: Background/Aims: We aimed to define the dosing and risk factors for death in patients undergoing twice-weekly hemodialysis. Methods: A prospective multi-center cohort study was conducted with one-year observation. Patients treated with twice- or thrice-weekly hemodialysis were identified. Death and first admission were the outcomes. spKt/V was a factor of interest. Results: We enrolled 504 twice-weekly and 169 thrice-weekly hemodialysis patients. The mean weekly values of spKt/V in the two groups were 3.4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 25 publications
1
36
0
Order By: Relevance
“…Overall, 16 studies, including 15 observational studies and one cross‐sectional study, with a total of 252 330 patients met the criteria for inclusion . Details of the literature search and study selection are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 16 studies, including 15 observational studies and one cross‐sectional study, with a total of 252 330 patients met the criteria for inclusion . Details of the literature search and study selection are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…As far as 1999, data from the American national sample have found that twice-weekly HD had similar or even better survival compared to thrice-weekly HD either in prevalent patients or in incident patients [2]. Panaput conducted a prospective multi-center cohort study in Thailand, the results indicated that survival rate and times to hospitalization between the two groups were similar [6]. We also reported that twice-weekly HD patients had no inferior survival as compared with thrice-weekly HD in Shanghai [11].…”
Section: Discussionmentioning
confidence: 99%
“…In China, about a quarter of the HD population receives twice-weekly HD [4], the proportion of this treatment regimen may be even higher in south Asia countries [5]. Few countries, such as Thailand, only twice-weekly HD could be covered by medical insurance [6]. Recently an incremental hemodialysis model with initiation of twice-weekly HD for incident patients has been advised in order to preserve the residual renal function better and to maximize the use of medical resource [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the NKF/KDOQI clinical practice guidelines recommended a minimum single pool Kt / V of 1.2 for thrice‐weekly HD patients with little or no RKF and a minimum weekly standardized Kt / V (i.e., a combined weekly urea clearance by HD and RKF) of 2.1 (), the dialysis dose for twice‐weekly HD patients is supported by few compelling studies. In a prospective cohort study (), the average weekly sp Kt / V in patients on twice‐weekly and thrice‐weekly HD were 3.4 and 5.1, respectively. However, no association of higher sp Kt / V with short‐term mortality was found in twice‐weekly HD (HR=0.6, 95% CI: 0.2–1.7, p = 0.7).…”
Section: Potential Unfavorable Effect Of Twice‐weekly Dialysismentioning
confidence: 99%